1996
DOI: 10.1007/bf02267046
|View full text |Cite
|
Sign up to set email alerts
|

Kinship, courtship, and child maintenance law in Botswana

Abstract: ABSTRACt. Official statistics in Botswana suggest very high numbers of extramarital births and female-heeded households. One element of family policy in Botswana is a statute allowing women to claim maintenance payments from the biological fathers of their extramarital children. Formal interviews and informal conversations with women and men in a village in Botswana indicate that women do not make use of the maintenance law for a variety of reasons. Among these is that a continuing tie to the biological father… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Even though it has been observed that married life in Africa is quite fragile, in comparison to studies that examine other aspects of family processes such as gender and reproductive relations (see for example, Addai, 1999Addai, , 2000Dodoo, 1993aDodoo, , b, 1998Ezeh, 1993;Oheneba-Sakyi & Takyi, 1991, 1997, or family policies (see e.g., Garey & Townsend, 1996;Randolph & Hassan, 1996;Van Hook & Ngwenya, 1996), literature on marital disruption in Africa and the forces that are behind the reported changes are somewhat rudimentary (for some exceptions, see Takyi, 2001). Thus we know very little about the determinants of marital instability, especially divorce in the region.…”
Section: Theoretical Perspectivesmentioning
confidence: 97%
“…Even though it has been observed that married life in Africa is quite fragile, in comparison to studies that examine other aspects of family processes such as gender and reproductive relations (see for example, Addai, 1999Addai, , 2000Dodoo, 1993aDodoo, , b, 1998Ezeh, 1993;Oheneba-Sakyi & Takyi, 1991, 1997, or family policies (see e.g., Garey & Townsend, 1996;Randolph & Hassan, 1996;Van Hook & Ngwenya, 1996), literature on marital disruption in Africa and the forces that are behind the reported changes are somewhat rudimentary (for some exceptions, see Takyi, 2001). Thus we know very little about the determinants of marital instability, especially divorce in the region.…”
Section: Theoretical Perspectivesmentioning
confidence: 97%
“…The role of kin is so important that, even where child support is mandated by law, women are reluctant to use it in favour of kin support. Garey and Townsend ( 1996 ) have argued that, in Botswana, few women actually use the child support mechanism because it interferes with traditional mechanisms of support for their children (i.e., extended kin) and can jeopardize the women’s chances of eventual marriage with the biological fathers or another man.…”
Section: Determinants Of Fathers’ Support Provisionmentioning
confidence: 99%
“…This comparison will also suggest that later industrializing countries may follow quite different gender paths as the structures of their separate spheres weaken. Some might cling to their gendered roles, maintaining a gender "essentialist" role structure (Brinton and Lee, forthcoming); others may minimize their gender differentiation, despite the strong impetus towards the separate spheres provided by the early industrializers (Boserup 1970;Garey and Townsend 1996;Thornton 2005). Even the early industrializers are making rapid headway towards much more equal gender roles, i.e., toward the complete destruction of the separate spheres.…”
Section: Introductionmentioning
confidence: 99%